Associations between parental mediation and adolescents' internet addiction: The role of parent–child relationship and adolescents' grades - Li, Xiaojing; Ding, Ying; Bai, Xianchun; Liu, Lisha (Frontiers in Psychology, 2022)
Introduction Family factors, such as parental mediation on Internet use and parent-child relationships, have been shown to play a crucial role in preventing adolescents' internet addiction. Previous studies have shown a change in characteristics of online risk during adolescents' development. However, it is still of great interest whether such differences applied in the relationships among parent-child relationships, different types of parental mediation and adolescents' internet addiction level. In this study, we investigated the associations between different types of parental mediators and adolescents' internet addiction level and how the associations were mediated by father-child and mother-child relationships. We further investigated whether mediating effect differs between primary and secondary school children. Methods Based on a sample of 3,026 school children aged 9–14 years (M = 11.56, SD = 0.71; 55.25% primary school adolescents, 44.75% secondary school adolescents), a series of Structural Equation Models were applied to investigate the relationships among internet addiction, parental mediation, and parent-child relationship. In addition, a series of multi-group analysis were applied to detect whether there are differences in these relationships between the primary and secondary school group. Results The internet addiction level and intensity of parental mediation was higher among primary school adolescents than secondary school adolescents. Parental active mediation and monitoring on internet use were associated with reduced and increased adolescents' internet addiction. Father-child relationship had stronger partial mediating effects on the relationships between parental mediation and adolescents' internet addiction than the mother-child relationship. The relationships among parental mediation, parent-child relationship and internet addiction were more pronounced among primary school adolescents than secondary school adolescents. Discussion The findings suggest that good father-child relationships and adequate parental mediation approach, such as active mediation, may contribute to reduction of internet addiction risk in adolescents, especially in primary school adolescents.